2019
DOI: 10.2217/pme-2019-0059
|View full text |Cite
|
Sign up to set email alerts
|

Potential Regulatory SNPs in the ATXN7L3B and KRT15 Genes are Associated with Gender-Specific Colorectal Cancer Risk

Abstract: Aim: According to the current data, a major factor for phenotypic variation of complex traits and disease susceptibility is the cis-acting effects of noncoding variants on gene expression. Our purpose was to evaluate the association between colorectal cancer (CRC) and six single nucleotide polymorphisms identified using our original bioinformatics approach as regulatory and putatively related to CRC. Materials: One hundred and sixty CRC patients and 185 healthy controls have been genotyped for rs590352, rs2072… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Both lncRNAs formed a ceRNA relationship with the mRNA ATXN7L3B and formed ceRNA relationships with some other mRNAs, respectively. ATXN7L3B have been confirmed to be associated with an increased risk of colorectal cancer ( Leberfarb et al, 2020 ), and cytoplasmic ATXN7L3B interfered with the nuclear functions of the SAGA deubiquitinase module ( Li et al, 2016 ). The SAGA complex was composed of two enzymatic modules, which house histone acetyltransferase (HAT) and deubiquitinase (DUB) activities.…”
Section: Resultsmentioning
confidence: 99%
“…Both lncRNAs formed a ceRNA relationship with the mRNA ATXN7L3B and formed ceRNA relationships with some other mRNAs, respectively. ATXN7L3B have been confirmed to be associated with an increased risk of colorectal cancer ( Leberfarb et al, 2020 ), and cytoplasmic ATXN7L3B interfered with the nuclear functions of the SAGA deubiquitinase module ( Li et al, 2016 ). The SAGA complex was composed of two enzymatic modules, which house histone acetyltransferase (HAT) and deubiquitinase (DUB) activities.…”
Section: Resultsmentioning
confidence: 99%
“…Genotyping of CRC patients and healthy controls according to six of these polymorphisms demonstrated that rs590352 of ATXN7L3B gene was associated with CRC in men and rs4796672 of KRT15 gene, with CRC in women. In addition, the analysis of haplotypes shows that rs2072580, located in the promoter region common for the ISCU and SART3 genes, can be also associated with CRC [ 174 ].…”
Section: Rsnps On a Genome-wide Scalementioning
confidence: 99%
“…Another 30 rSNPs have been implicated in colorectal cancer with the help of data from the International Cancer Ge nome Consortium (ICGC) (Seshagiri et al, 2012). Genotyping of patients with colorectal cancer and healthy individuals for six of these SNPs has revealed an association of rs590352, rs4796672, and rs2072580 with this disease (Leberfarb et al, 2020). A correlation with breast cancer has been found for rs2072580 (Degtyareva et al, 2020).…”
mentioning
confidence: 99%